The Comparative analysis on the impact of three major diseases in the cocoa crop CCN-51, in La Troncal, Cañar province, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2018)
This study analyzed the distribution of three main diseases of cacao CCN-51: moniliasis (Moniliophthora roreri), witch’s broom (Crinipellis perniciosa) and black cob (Phytophthora palmivora) in the precincts of the parishes San Antonio and Pancho Negro, of La Troncal, Cañar Province, Ecuador. Ruidoso Chico (911,9 ha) and Diez de Agosto (525,25 ha) comprise 48,38% of production in the area of 2970,21 hectares. La Envidia and San Luis have the older plantations, with 40 years of cultivation. The maximum yield is in La Envidia and Cuarenta Cuadras that reach 4000 kg/ha/year. The most affected sectors by M. roreri, C. pernicious and P. palmivora are Caimatán, Manta Real and Zhucay, where these diseases are located in the 100% of the plantations. The incidence of C. perniciosa and P. palmivora decays gradually, to the point of sectors such as Copalillos, La Grecia, La Pista, Las Mercedes and San Felipe, where there is total absence of these diseases. In all cases, it is evident that moniliasis is the disease that most affects the area.
Keywords: epiphyte; phytopathogen; fungus; inoculum; mycelium